INOVASI PEMBELAJARAN MATEMATIKA PADA SD NEGERI 230 MALUKU TENGAH BERBASIS KEARIFAN LOKAL - Lesnussa, Yopi Andry; Wattimury, Welminci W; Salamahu, Leberima; Matdoan, M Y (Universitas Pattimura, 2023)
Mathematics learning activities at SD Negeri 230 Maluku Tengah is a form of community service activity from a series of Teaching Assistance activities carried out by Pattimura University. From the results of the mathematics learning activities on 28 students in grade 5 and grade 6 at SD Negeri 230 Maluku Tengah, it was found that there was a significant increase from the pre-test results. Where the value of the post-test results is higher than the pre-test results, then according to statistics descriptive there is a difference in the average student learning outcomes before being given training (pre-test) with student learning outcomes after being given training (post-test). The test results with the pair sample test method obtained a significance value (Sig.) of 0.038 <0.05, so it can be concluded that there is a real difference (significant) in the average between the pre-test and post-test learning outcomes. Apart from that, learning materials raised from the local context also encourage and facilitate students in understanding the process of learning mathematics based on local wisdom